Wolf stalker - Skurzynski, Gloria; Ferguson, Alane (Washington, D.C. : National Geographic Society ; [Emeryville, CA] : Distributed by Publishers Group West, 1997)
Twelve-year-old Jack, his younger sister, and the family's teenage foster child Troy go to Yellowstone National Park, where Jack's mother, a wildlife veterinarian, is investigating the report that wolves reintroduced to the park have killed a dog there.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Map of Yellowstone National Park on end papers.
Description based on print version record.
Keywords: Wolves -- Fiction; Wildlife reintroduction -- Fiction; Wildlife conservation -- Fiction; Yellowstone National Park -- Fiction; National parks and reserves -- Fiction; Mystery and detective stories; Wolves -- Juvenile fiction; Wildlife reintroduction -- Juvenile fiction; Wildlife conservation -- Juvenile fiction; National parks and reserves -- Juvenile fiction; Detective and mystery stories; Yellowstone National Park -- Juvenile fiction; Electronic books- OSLIS; Electronic books